Abstract 191: Simulating Intracranial Stenosis: A Methodological Approach In An In‐Vitro Neurovascular Model - Riccardo Daniel Tiberi; Jiahui Li; Joan Vargas; Magda Jablonska; Judith Cendrero; Pere Canals; Marc Molina; Alejandro Tomasello; Marc Ribo (Stroke: Vascular and Interventional Neurology)
Introduction Intracranial atherosclerotic disease (ICAD) induces the luminal narrowing of an intracranial vessel and represents one of the major causes of ischemic strokes [1, 2, 3, 4]. In vitro 3D printed models have gained popularity in the stroke research field as they are morphologically accurate and offer the possibility to simulate clinical scenarios for training purposes or device testing. Despite being a challenge for interventionalists, to date, clinically accurate ICAD in vitro models have not been developed. We aimed to develop a 3D printed ICAD model including realistic features to provide an optimal simulation phantom for research and training purposes. Methods Stereolithography 3D printing technique was used to create a resin neurovascular model based on vascular anatomies extracted from anonymized CTA images. The phantom includes the aortic arch, all supraoptic cervical arteries and a complete circle of Willis up to the M2‐MCA, A2‐ACA and P2‐PCA segments. 3% sodium alginate solution was cast into a stenosis mold and crosslinked in a 40% calcium chloride. The deformable gel constituted an 8mm long replaceable stenotic segment at the level of M1‐MCA simulating an atherosclerotic plaque with a 0.5mm internal diameter. A flow sensor (ME‐8PXL, Transonic) was used to measure the lesion flow rate before and after endovascular treatment was performed under fluoroscopy. Results The baseline angiographic run showed an irregular 80% stenosis at the level of M1‐MCA that generated a substantial delay of contrast arrival to the distal branches. After angioplasty (Gateway PTA Balloon Catheter 3.5x20mm, Boston Scientific) and stenting (Wingspan 2.5mmx15mm, Stryker) were performed the residual stenosis was <10% (Figure 1). An initial stenosis flow rate was registered with a value of 8.5 ± 5.33 mL/min. Following the completion of the endovascular procedure, the flow sensor detected a post‐procedural stenosis flow rate of 160 ± 3.45 mL/min. Conclusion The developed ICAD model is anatomically accurate and offers realistic physiological and procedural features. The phantom represents an ideal tool for training purposes and a platform to test different devices for the endovascular treatment of ICAD. The methodology and materials could be applied to simulate stenotic lesions at different levels in the cervical and intracranial arteries.